INNOVATIVE METHODS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (EFL) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines innovative methods used in teaching English as a Foreign Language (EFL) and analyzes their effectiveness in improving learners’ language competence. It focuses on communicative approaches, technology-enhanced learning, interactive techniques, project-based learning, and student-centered instruction. Unlike traditional grammar-translation methods, modern pedagogical approaches aim to develop learners’ practical language skills and communicative competence. The article highlights the importance of increasing student engagement, motivation, and real-life language application in EFL classrooms. Furthermore, it discusses the role of teachers in implementing innovative strategies and adapting them to learners’ needs in a rapidly changing educational environment.